Optimization of Used Gallons for Catfish and Horticultural Crop Cultivation in a Simple System - Yulianita, Dhea; Setiyadewi, Nafa Aswanda; Ardhinesa, Renara Daffa; Anugrah, Fajar Aji; Azalia, Talita Zerlina; Aizah, Anis Winji; Anifah, Nur; Septiawan, Krisna Dwi; Paramarta, Hagil Malik; Utami, Kandela Intan (Proceedings Series on Social Sciences & Humanities, 2025)
The optimization program of used gallons for cultivation of catfish and horticultural crops in a simple system aims to utilize inorganic waste while increasing food security and community economy. The activity was carried out in Karanganyar Village, Sukoharjo District, Wonosobo Regency, targeting the Head of the RT. The method used was socialization and training in making aquaponic-based cultivation installations, where used gallons were modified into catfish containers and vegetable planting media such as pakcoy, chili, and tomatoes. This system utilizes fish metabolic waste as a natural fertilizer for plants, thus creating an integrated cultivation cycle that saves water, minimizes waste, and is environmentally friendly. The results showed optimal fish and plant growth, increased community knowledge on plastic waste management, as well as opportunities for savings and additional household income. The program proved to be easy to implement, inexpensive, and has the potential to be a sustainable solution to address environmental issues and support the availability of nutritious food.